2002
DOI: 10.1038/nrc780
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB in cancer: from innocent bystander to major culprit

Abstract: Nuclear factor of kappaB (NF-kappaB) is a sequence-specific transcription factor that is known to be involved in the inflammatory and innate immune responses. Although the importance of NF-KB in immunity is undisputed, recent evidence indicates that NF-kappaB and the signalling pathways that are involved in its activation are also important for tumour development. NF-kappaB should therefore receive as much attention from cancer researchers as it has already from immunologists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

42
1,971
3
18

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 2,348 publications
(2,053 citation statements)
references
References 96 publications
42
1,971
3
18
Order By: Relevance
“…Consistent with a role for IKKa in promoting cyclin D1 transcription, Karin et al (2002) have found that during mammary gland development IKKa is required for RANK signaling and cyclin D1 expression. Other mechanisms whereby NF-kB may potentiate cancer cell growth is through its reported requirement for the upregulation of HIF-1a (Jung et al, 2003) and its regulation of c-myc transcription (see Baldwin 2001;Karin et al, 2002). Consistent with these reports, tumor growth in several mouse xenograft models is impaired when NF-kB is inhibited (see Reuther et al, 1998;Baldwin, 2001;Karin et al, 2002).…”
Section: Growth and Proliferationsupporting
confidence: 55%
See 2 more Smart Citations
“…Consistent with a role for IKKa in promoting cyclin D1 transcription, Karin et al (2002) have found that during mammary gland development IKKa is required for RANK signaling and cyclin D1 expression. Other mechanisms whereby NF-kB may potentiate cancer cell growth is through its reported requirement for the upregulation of HIF-1a (Jung et al, 2003) and its regulation of c-myc transcription (see Baldwin 2001;Karin et al, 2002). Consistent with these reports, tumor growth in several mouse xenograft models is impaired when NF-kB is inhibited (see Reuther et al, 1998;Baldwin, 2001;Karin et al, 2002).…”
Section: Growth and Proliferationsupporting
confidence: 55%
“…Furthermore, IKKa has been proposed to play a role in cyclin D1 transcription through a T-cell factor site in the promoter, via its ability to control b-catenin phosphorylation (Albanese et al, 2003). Consistent with a role for IKKa in promoting cyclin D1 transcription, Karin et al (2002) have found that during mammary gland development IKKa is required for RANK signaling and cyclin D1 expression. Other mechanisms whereby NF-kB may potentiate cancer cell growth is through its reported requirement for the upregulation of HIF-1a (Jung et al, 2003) and its regulation of c-myc transcription (see Baldwin 2001;Karin et al, 2002).…”
Section: Growth and Proliferationmentioning
confidence: 71%
See 1 more Smart Citation
“…The NF-κB system comprises a family of transcription factors that are held inactive in the cytoplasm by a family of inhibitory proteins known as IκBs 75 . These inhibitors are ubiquitylated and degraded by a phosphorylation event that is triggered by the IκB kinase (IKK).…”
mentioning
confidence: 99%
“…It is assembled as a hetero-or homodimer from the structurally closely related subunits RelA/p65, c-Rel, RelB, p50 and p52 (Karin et al, 2002).…”
mentioning
confidence: 99%